Pengaruh Konseling Behavioristik terhadap Academic Hardiness Siswa MAN 2 Bukittinggi - Yeni Febrianti; Fadhilla Yusri (Lembaga Yasin AlSys, 2026)
Low academic hardiness among some students at MAN 2 Bukittinggi was indicated by their tendency to give up easily when facing learning difficulties, limited self-control in dealing with academic challenges, and low commitment to completing school assignments. This study aimed to analyze the effect of behavioral counseling on the academic hardiness of students at MAN 2 Bukittinggi. The study employed a quantitative approach using a pre-experimental method and a one-group pretest–posttest design. The research population consisted of 125 Grade X students, while the sample comprised eight students selected through purposive sampling. Data were collected using an academic hardiness questionnaire developed by the researchers and analyzed using the Wilcoxon signed-rank test with SPSS version 26. The results showed that all students experienced an increase in academic hardiness after participating in behavioral counseling. The mean score increased from 72.75 on the pretest to 134.625 on the posttest, with all students classified in the high category after the intervention. The hypothesis test yielded an Asymp. Sig. (2-tailed) value of 0.012 < 0.05, indicating a significant difference between the conditions before and after the intervention. Thus, behavioral counseling had a significant effect on improving students’ academic hardiness. These findings provide practical implications for Guidance and Counseling teachers to use behavioral counseling as an alternative service for improving students’ commitment, self-control, and ability to face academic challenges.